The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.3892/ijo.30.6.1359
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hypoxia-inducible factor-1 alpha and associated proteins in pancreatic ductal adenocarcinoma and their impact on prognosis

Abstract: Abstract. The aim of this study was to assess the significance of expression of hypoxia-inducible factor-1α (HIF-1α) and associated proteins in pancreatic ductal adenocarcinoma (PDA) and their impact on prognosis. Expression of HIF-1α, vascular endothelial growth factor (VEGF), glucose transporter-1 (Glut-1), survivin, CD34 and Ki-67 and apoptotic cells was demonstrated by immunohistochemistry or TUNEL in 58 PDAs and 20 normal pancreatic tissue samples. Our results show positivity of HIF-1α, VEGF, Glut-1 and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
103
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(116 citation statements)
references
References 28 publications
5
103
1
2
Order By: Relevance
“…A correlation between hypoxia and pancreatic cancer has been recognized for a number of years (21), and a role for HIF-1a and HIF-2a in pancreatic cancer has previously been investigated (22,23). In this study, we showed that HIF-3a expression is stimulated to a greater extent than either HIF-1a or HIF-2a under hypoxic conditions in pancreatic cancer cells.…”
Section: Discussionsupporting
confidence: 56%
“…A correlation between hypoxia and pancreatic cancer has been recognized for a number of years (21), and a role for HIF-1a and HIF-2a in pancreatic cancer has previously been investigated (22,23). In this study, we showed that HIF-3a expression is stimulated to a greater extent than either HIF-1a or HIF-2a under hypoxic conditions in pancreatic cancer cells.…”
Section: Discussionsupporting
confidence: 56%
“…In favor of this hypothesis are results from a recently published study demonstrating that KRAS activation promotes KLF5 up-regulation in human colon cancer (HCT116) cells (13). Moreover, because hypoxia-mediated and cytokine-mediated activation of the oncogenic transcription factor hypoxia-inducible factor-1α (HIF-1α) is frequently encountered in pancreatic tumors, we also hypothesized that the interleukin (IL)-1β system and/or HIF-1α may be involved in the regulation of KLF5 expression (14)(15)(16)(17)(18). We therefore sought to further define the expression and regulation of KLF5 in human pancreatic cancer cells to expand our knowledge on this particular transcription factor and to potentially reveal a novel molecular therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it hampers the delivery of oxygen, causing hypoxia [11]. Such a hypoxic microenvironment diminishes sensitivity to chemotherapeutics and radiation and negatively impacts prognosis [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%